2021
DOI: 10.3390/ijms22136919
|View full text |Cite
|
Sign up to set email alerts
|

n-6 High Fat Diet Induces Gut Microbiome Dysbiosis and Colonic Inflammation

Abstract: Background: Concerns are emerging that a high-fat diet rich in n-6 PUFA (n-6HFD) may alter gut microbiome and increase the risk of intestinal disorders. Research is needed to model the relationships between consumption of an n-6HFD starting at weaning and development of gut dysbiosis and colonic inflammation in adulthood. We used a C57BL/6J mouse model to compare the effects of exposure to a typical American Western diet (WD) providing 58.4%, 27.8%, and 13.7% energy (%E) from carbohydrates, fat, and protein, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…There were no correlations between gut bacteria and n6 fatty acids, but there was a negative correlation between EPA and Lachnospiraceae . Selmin et al found a reduction in Lachnospiraceae after a n6 high-fat diet in mice [ 30 ]. Others have shown a positive correlation between circulating levels of docosahexaenoic acid (DHA) (C22:6n3) and Lachnospiraceae [ 29 ] and an increase in several butyrate-producing bacteria in the Lachnospiraceae family after intervention with a n3 fatty acid-rich diet in adult males [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no correlations between gut bacteria and n6 fatty acids, but there was a negative correlation between EPA and Lachnospiraceae . Selmin et al found a reduction in Lachnospiraceae after a n6 high-fat diet in mice [ 30 ]. Others have shown a positive correlation between circulating levels of docosahexaenoic acid (DHA) (C22:6n3) and Lachnospiraceae [ 29 ] and an increase in several butyrate-producing bacteria in the Lachnospiraceae family after intervention with a n3 fatty acid-rich diet in adult males [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A correlation between omega-3 (n3) fatty acids and gut microbiota [ 27 , 28 ], including a positive correlation with bacteria of the Lachnospiraceae family [ 28 , 29 ], has been reported. In a recent study in mice, an omega-6 (n6) high-fat diet induced changes in gut microbiota, including a reduction in Lachnospiraceae [ 30 ]. However, only a few studies have investigated the effect of fat quality on gut microbiota and the impact on human metabolic regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Mucispirillum schaedleri is detected in a variety of mammals, and it is known to have low relative abundance of the intestinal microbiota in murine feces ( Herp et al., 2021 ). An increasing number of certain bacterial species have been associated with inflammatory conditions in the gut ( Selmin et al., 2021 ). Parabacteroides gordonii is one of the several gut bacteria with anti-inflammatory attributes ( Abais-Battad et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In effect, it has been established that its moderate intake is able to reduce total cholesterol and LDL concentrations [10] and to prevent the risk of development of cardiovascular disease [10,11]. However, the role of omega-6 metabolites is clearer, because they are involved in the inflammatory process in response to air pollution [12], and cause a shift in the microbiota, contributing to an increase of colonic inflammation [13]. Finally, a higher omega-6 dietary intake has been associated to an increase of pro inflammatory metabolites [14].…”
Section: Discussionmentioning
confidence: 99%